International support for the Arab uprisings: Understanding sympathetic collective action using theories of social dominance and social identity. (January 2016) - Stewart, Andrew L.; Pratto, Felicia; Bou Zeineddine, Fouad; Sweetman, Joseph; Eicher, Véronique; Licata, Laurent; Morselli, Davide; Saab, Rim; Aiello, Antonio; Chryssochoou, Xenia; Cichocka, Aleksandra; Cidam, Atilla; et al.
Inspired by the popular Arab protests against oppressive regimes that began in 2010, people around the world protested in sympathy with the Arab peoples. The present research draws on two major theories of intergroup relations to develop an initial integrative model of sympathetic collective action. We incorporate social dominance theory's (SDT) concept of (rejectionist) legitimizing myths with the solidarity and emotional mediation concept of the social identity model of collective action (SIMCA) to understand motivations for sympathetic collective action among bystanders. Using data from 12 nations ( N = 1, 480), we tested three models: (a) SIMCA (i.e., solidarity, anger, and efficacy), (b) a social dominance theory model of collective action (i.e., social dominance orientation and ideologies concerning Arab competence), and (c) an integrated model of sympathetic collective action combining both theories. Results find the greatest support for an integrated model of collective action. Discussion focuses on theoretical pluralism and suggestions for future research.